2017
DOI: 10.1155/2017/9286392
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Diagnosis of Malaria: Comparison of Manual and Automated Diagnostic Tests

Abstract: Malaria is the second most prevalent disease in Pakistan resulting in ~30,000 annual deaths. In endemic countries like Pakistan precise and timely diagnosis of malaria is imperative to overcome the associated risks of fatal outcomes. Malarial parasite was screened in 128 malaria suspected patients and 150 healthy controls, by species-specific PCR, microscopy of blood smears, hemoanalyzer Sysmex XE-2100, and rapid test devices (First Response Malaria® and ICT Malaria Combo®). The microscopy detected MP in 126 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…3,4 Notwithstanding the widespread availability of specific external quality assessment programs (EQAs), the low incidence of new diagnoses in Western countries does not allow to maintain a satisfactory degree of expertise for identifying Malaria parasites with microscopic revision of blood smears, so that screening techniques for a targeted microscopic review may be necessary for enabling an early and accurate diagnosis of this infection, especially in nonendemic countries. 3 Recent evidence attests that the latest generation of hematological analyzers may be a valid support for the screening of patients with suspected Malaria, [5][6][7][8][9][10][11][12][13][14][15] although the diagnostic sensitivity and specificity of abnormal findings were found to be strictly dependent on the instrumentation, the parasitic index, and the stage of Plasmodium maturation. The most suggestive findings that have been described so far include abnormalities of leukocyte differential scattergram and reticulocyte (RET) count, which may indicate the presence of parasites at various stages of maturation (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Notwithstanding the widespread availability of specific external quality assessment programs (EQAs), the low incidence of new diagnoses in Western countries does not allow to maintain a satisfactory degree of expertise for identifying Malaria parasites with microscopic revision of blood smears, so that screening techniques for a targeted microscopic review may be necessary for enabling an early and accurate diagnosis of this infection, especially in nonendemic countries. 3 Recent evidence attests that the latest generation of hematological analyzers may be a valid support for the screening of patients with suspected Malaria, [5][6][7][8][9][10][11][12][13][14][15] although the diagnostic sensitivity and specificity of abnormal findings were found to be strictly dependent on the instrumentation, the parasitic index, and the stage of Plasmodium maturation. The most suggestive findings that have been described so far include abnormalities of leukocyte differential scattergram and reticulocyte (RET) count, which may indicate the presence of parasites at various stages of maturation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…trophozoites, schizos, and gametocytes). [5][6][7][8][9][10][11][12][13][14][15] The new hematological analyzer Sysmex XN-module (Sysmex Co., Kobe, Japan) enumerates and classifies blood cells, RET, immature leukocytes (White Precursors Cell; WPC), and platelets (PLT) with a combination of optical fluorescence technique (PLT-F), flow cytometry, and laser-optical recognition. The XN-module also provides a variety of innovative cell population data (CPD) parameters, which can be helpful for improving leukocyte differential count and for the more accurate identification of abnormal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Bhavnaben A. Vora et al 9 in their comparative study, Peripheral smear had 85.5% sensitive and 100% specific compared to RDT which was 100 % sensitive and specific whereas centrifuged buffy coat was 92.7% sensitive and 99.3% specific. Samina Naz Mukry et al 10 concluded in their study that RDT with a sensitivity of 91.52%. Manali M. Kocharekar et al 11 studied the efficacy of RDT and concluded the sensitivity of Parahit total, Advantage mal card, and modified QBC for P. falciparum detection was 70.3%, 95%, and 98%, and specificity was 98%, 98%, and 96%, respectively.…”
Section: Comparison Of Smear Microscopy and Rapid Diagnosticmentioning
confidence: 97%
“…In the thin blood smear, the degree of parasitemia, the appearance of pigments in leukocytes, the number of thrombocytes, and other possible hematological changes can be assessed as well. A well-educated parasitologist, standardized laboratory procedures, and enough time to review are preconditions for quality performance reviews [8].…”
Section: Accepted Diagnostic Proceduresmentioning
confidence: 99%